Codename Geronimo: settler memory and the production of American statism. (1st October 2016) - Bruyneel, Kevin
ABSTRACT: The article examines the use of the name 'Geronimo' as the codename that the US Defense Department gave to Osama Bin Laden in their successful mission to assassinate him. In engaging this critique of "Codename Geronimo, " the article offers a way to imagine decolonization and unsettlement through a wider critique of American statism, upon the premise that anti-statism is a necessary component of a decolonizing, unsettling politics. The article argues that American state practices and institutions function and are legitimated, especially in their most warlike functioning, through settler memory. Settler memory is an active practice, not a reference to dislocated past. The American effort to legitimate settlement requires persistent articulation, especially as it concerns statist power that enforces and naturalizes Indigenous territorial dispossession and Indigenous people's disempowerment. Settler memory is critical to the reproduction of settler colonial assemblage, and thus it must be centered more in our effort to grasp and critique American state practices.